Isolated tubal torsion associated with hydrosalpinx - Esra Tamburaci (IMR Press, 2022)
Background: Isolated tubal torsion associated with hydrosalpinx is a rare pathology. Our aim was to analyze clinical and imaging features. Case: A 15-year-old girl was admitted to the gynecological emergency department with lower abdominal pain. She was virgin and did not have gynecological examination. In ultrasonography a 10 cm cystic lumen was observed in the right tube. Right salpingectomy was performed. In the pathological examination, there was ischemic changes due to torsion. Conclusion: Isolated tubal torsion is extremely rare in early adolescent period. Early surgical intervention after diagnosis is important for fertility.